Short-term outcomes of enhanced recovery after surgery protocol in robotic-assisted McKeown esophagectomy for esophageal cancer: a single-center retrospective cohort study - Xu, Xia; Xiong, Jiajun; Xu, Zhijie; Hu, Zhi; Alai, Guha; Yu, Lulu; Xia, Shaofeng; Lin, Yidan (Frontiers in Oncology, 2023)
Background: This study aimed to evaluate the short-term outcomes of enhanced recovery after surgery (ERAS) protocol in perioperative robotic-assisted McKeown esophagectomy (RAME) among esophageal cancer patients. Materials and methods: For this retrospective study, all patients who had undergone RAME with esophageal cancer using ERAS protocol and conventional management strategy at the surgery center of our hospital, from February 2019 to March 2022 were performed for analysis. Results: A total of 211 patients were included. Compared to the conventional group, the ERAS group has shorter median operative time [207 (147.5-267.5) vs. 244 (183-305), P<0.001], time to first flatus (P<0.001), time to out-of-bed activity (P=0.045), and time to liquid diet (P<0.001). In addition, the ERAS group has lower postoperative pain scores (3.62 ± 0.87 vs. 4.54 ± 0.91), shorter duration of analgesia pump [2 (1-3) vs. 3 (2.5-5.5)], shorter postoperative hospital stay [(9 (6-47) vs. 11 (6-79)], and shorter postoperative ICU stay [1 (0-7) vs. 2 (0-15)]. Furthermore, the overall complication rate was significantly lower in the ERAS group (26.1%) than in the conventional group (50.4%). Notably, the ERAS group had lower thoracic fluid drainage volume than the conventional group on postoperative 2-7 days (P<0.05). Conclusion: The application of ERAS protocol in esophageal cancer patients treated with RAME showed advantages of quick postoperative recovery in contrast to the conventional management strategy.